FUNGSI PENGAWASAN INSPEKTORAT PADA APARATUR PEMERINTAH DI KECAMATAN AMURANG TIMUR KABUPATEN MINAHASA SELATAN - Denje, Agnes Hardianti; Posumah, Jhonny Hanny; Rares, Joyce Jacinta (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT :The fact that the large volume of work and endured by the apparatus was tough because ofthe limited number of personnel, the state apparatus thus indeed requires a skilled, resilient, and high qualityof the duties and responsibilities. One way that can be done to create such apparatus is supervised todetermine the results of the assessment of performance, namely by doing a systematic evaluation of theresults of monitoring reports has been delayed. Performance of the apparatus can be influenced by manyfactors, including the standard-setting work, operational implementation of the work, and the implementationof the mechanism of action. The purpose of this study was to inspectorate functions Controlling in thegovernment apparatusin the district Amurang sout he ast county minahasa.So thisprompted theauthorstoseethe implementation of Structural and Functional oversight function in the South MinahasaDistrict Inspectorate. This problem is limited to asupervisory roleon the functional and structural monitoringapparatus in Amurang eastern district shaverun optimally.Keywords : Controlling, Inspectorate, Apparatus